2020
DOI: 10.3390/ani10050885
|View full text |Cite
|
Sign up to set email alerts
|

Effects on the Ileal Microbiota of Phosphorus and Calcium Utilization, Bird Performance, and Gender in Japanese Quail

Abstract: In this study, we aimed to investigate the ileum digesta of a large cohort of Japanese quail fed the same diet, with similar environmental conditions. We also address how P utilization (PU), Ca utilization (CaU), and bird performance (feed intake (FI), feed conversion (FC), and body weight gain (BWG)) modify intestinal microbiota of male and female quail. Despite the great number of samples analyzed (760), a core microbiome was composed of five bacteria. The Unc. Lactobacillus, Unc. Clostridaceae 1, Clostridiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 51 publications
3
19
1
2
Order By: Relevance
“…They account for 96% of the total community. Further details regarding the microbiota characteristic are presented in ( Borda-Molina et al , 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They account for 96% of the total community. Further details regarding the microbiota characteristic are presented in ( Borda-Molina et al , 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Ileum microbial composition was obtained from a previous study ( Borda-Molina et al , 2020 ). Briefly, ileum digesta samples of 760 quails were sequenced using 250bp paired-end sequencing chemistry on an Ilumina MiSeq platform (128 samples did not pass the quality filter of the sequences and were subsequently discarded).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the role of the structure and composition of the intestinal microbiota on the intestinal mucus layer and structure in ducks remains unclear. Furthermore, some studies have suggested the existence of sex-dependent effects on the intestinal microbiota in various animal models ( McKenna et al, 2008 ; Yurkovetskiy et al, 2013 ; Bolnick et al, 2014 ; Borda-Molina et al, 2020 ). Under normal circumstances, males grow faster than females, probably due to sexual differences in growth and development ( Osei-Amponsah et al, 2012 ; Benyi et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Operational taxonomic units (OTUs) deduced from 16S rRNA sequencing of the same animals were obtained from a recent study (access number PREJB37544) [63]. Initially, OTUs were assigned to taxa at the genus level and OTU counts belonging to the same genera were summarized.…”
Section: Microbiome Data Analysismentioning
confidence: 99%